НЕМИС ТИЛИ САБАҒЫНДА ПЕДАГОГИКАЛЫҚ ТЕХНОЛОГИЯЛАРДАН ПАЙДАЛАНЫЎДА АНА ТИЛИНИҢ ТӘСИРИ - Есбергенова, Г.Б. (SCIENCE and SOCIETY, 2021)
In the article the gist of pedagogical technologies in educating the foreign languages in current elementary classes are discussed. As well, the interactive methods are recommended in the process of teaching and the due competencies of teachers.
Keywords: mother tongue; speech; education; content; psychological and pedagogical training; method